On extrapolation of virial coefficients of hard spheres - Ončák, M.; Malijevský, A.; Kolafa, J.; Labík, S. (Condensed Matter Physics, 2012)
Several methods of extrapolating the virial coefficients, including those proposed in this work, are discussed. The methods are demonstrated on predicting higher virial coefficients of one-component hard spheres. Estimated values of the eleventh to fifteenth virial coefficients are suggested. It has been speculated that the virial coefficients, Bn, beyond B₁₄ may decrease with increasing n, and may reach negative values at large n. The extrapolation techniques may be utilized in other fields of science where the art of extrapolation plays a role.